2009
DOI: 10.2465/jmps.080506
|View full text |Cite
|
Sign up to set email alerts
|

Role of geochemical alteration on the formation of secondary Zr- and U-bearing minerals in El Atshan trachyte, central Eastern Desert, Egypt

Abstract: El Atshan area, situated in the central Eastern Desert of Egypt, is a good location for studying the influence of high -and low -T alterations on the formation of Zr -and U -bearing minerals within a trachyte sill. These minerals are mainly represented by an unidentified secondary Zr -rich silicate mineral, betafite, and liandratite. The unidentified Zr -rich silicate mineral is considered to be an alteration product of the precursor zirconolite during high -T alteration. This is indicated by the changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Since its first description as a new mineral species, liandratite has only been mentioned by several authors (Lumpkin and Ewing 1996;Lumpkin 2001;Kristiansen 2006;Abd El-Naby 2009;Galliski et al 2009;Matyszczak 2013Matyszczak , 2014, while chemical data seem to have been presented only by Lumpkin and Ewing (1996). The latter authors found liandratite as a weathering product of betafite (□,U 4+ ) 2 Ti 2 O 6 (O,OH,F) and analyses revealed that the chemical composition of liandratite is no less complex than those of the other Nb-Ta-Ti oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description as a new mineral species, liandratite has only been mentioned by several authors (Lumpkin and Ewing 1996;Lumpkin 2001;Kristiansen 2006;Abd El-Naby 2009;Galliski et al 2009;Matyszczak 2013Matyszczak , 2014, while chemical data seem to have been presented only by Lumpkin and Ewing (1996). The latter authors found liandratite as a weathering product of betafite (□,U 4+ ) 2 Ti 2 O 6 (O,OH,F) and analyses revealed that the chemical composition of liandratite is no less complex than those of the other Nb-Ta-Ti oxides.…”
Section: Introductionmentioning
confidence: 99%